Assessing the effect of cleansing products on artificially polluted human hairs and skin through in vivo and in vitro models. Issue 1 (7th January 2023) - Galliano, Anthony; Ye, Chengda; Su, Fengjie; Wang, Chad; Rakshit, Rima; Guerin, Myriam; Flament, Frédéric; Steel, Andrew
Abstract: Objective: Based on in vivo data, in vitro models and new methods are created to mimic the impact of aerial pollution onto the hair surface and assess the efficacy of different formulae prototypes. Material and methods: Two protocols are developed to mimic the pollution effect, in vitro, on purchased swatches, and in vivo, on scalps and forearms. First, with an artificial sebum mixed with Carbon Black particles, named "sebollution, " we evaluated, through an instrumental color measurement, the cleansing efficacy of some shampoo on scalp and hair. The second protocol allowed to assess the interaction between hair care product deposit (shampoo, conditioner, mask, and leave‐on) on hair and carbon black particles spread on fiber. The quantification of particle coverage allowed to evaluate the efficiency of a formula to limit the aerial pollution deposit on hair fiber. Results: To simplify and accelerate the evaluation of 42 shampoo formulae, an extrapolation of the scalp cleaning process was validated on forearm. The respective cleanabilities were calculated and covered a large range of efficacy, from 5%, for a basic bland shampoo generally used to reset swatches, to a strong deep cleansing efficacy of 100%. On hair swatches, cleanability efficiencies of five shampoo were also evaluated to eliminate the deposited of sebollution, in a range of 40%–80%. To quantify the efficacy of preventing the deposition of carbon particle on hair surface, the percentage of coverage of 45 different products was measured, from 2% to 16%. The performance depended of the product category (shampoo, conditioner, mask, and leave‐on), driven by the performance of the product deposit, and the capacity of this deposit to interact with aerial pollution. Conclusion: Three new protocols and evaluation methods are proposed to evaluate and quantify the performance of hair care product, to remove/clean, limit, and protect the hair fibers against the aerial pollution that could interact with hair, scalp and sebum. The validation of these approaches was done through the testing of a large panel of hair care product leading to a complete and sincere evaluation of cleansing and anti‐deposit efficacy. Combining the knowledge acquired on pollution impact on hair and the development of specific way of evaluation, this work reinforced the rationale of using and developing new cosmetic products that reduced the impact of pollution upon some hair properties.